Stereoselective Isoxazolidine Synthesis Via Copper-Catalyzed Alkene Aminooxygenation - Karyakarte, Shuklendu D. (2012)
[Image: see text] Isoxazolidines are useful in organic synthesis, drug discovery and chemical biology endeavors. A new stereoselective synthesis of methyleneoxy-substituted isoxazolidines is disclosed. The method involves copper-catalyzed aminooxygenation/cyclization of N-sulfonyl-O-butenyl hydroxylamines in the presence of (2,2,6,6-tetramethylpiperidin-1-yl)oxyl radical (TEMPO) and O(2), and provides substituted isoxazolidines in excellent yields and diastereoselectivities. We also demonstrate selective mono N-O reduction followed by oxidation of the remaining N-O bond to reveal a 2-amino-γ-lactone. Reduction of the γ-lactone reveals the corresponding aminodiol.